PENGARUH MATRIKS DAN KETEBALAN SKIN TERHADAP SIFAT MEKANIK KOMPOSIT SANDWICH DENGAN CORE POLYURETHANE - Hestiawan, Hendri; Afrizal, Yuzuar; FA, A. Sofwan; Sitinjak, Heryanto; Fadilah, M. Hafidz (Universitas Muhammadiyah Metro, 2024)
Indonesia is an earthquake-prone country related to its geological position located in the Pacific ring of fire. Therefore, it is necessary to mitigate earthquake disasters so as not to cause much loss, both property and life. One of them is by introducing the walls of earthquake resistant composite house (RKTG) made from sandwich composites. The purpose of this study was to investigate the effect of matrix and skin thickness on the mechanical strength of sandwich composites with polyurethane cores.). Sandwich composites use variations of glassfiber reinforced polymer (GRP) and glassfiber reinforced concrete (GRC) skins and variations in skin thickness of 6 mm and 10 mm. The adhesive used is polyester resin with methyl ethyl ketone peroxide catalyst. The manufacturing process of making sandwich composites uses the hand lay-up technique with a sandwich composite thickness of 10 cm. The results showed that GRP skins have better mechanical properties than GRC skins. Skin thickness can also improve the mechanical properties of sandwich composites. The best mechanical strength was obtained in the GRP skin type with a skin thickness of 10 mm, namely a flexure strength of 1.63 MPa, a compressive strength of 10.7 MPa, and a tensile strength of 0.08 MPa.